Persepsi Penyuluh Pertanian terhadap Implementasi Undang-Undang Nomor 23 Tahun 2014 di Kabupaten Lampung Timur - Purnamawati, Tati; Nikmatullah, Dewangga; Gitosaputro, Sumaryo; Gultom, Dame Trully; Rangga, Kordiyana K (Fakultas Pertanian, Universitas Lampung, 2023)
Law Number 23 of 2014 resulted in the management of fisheries extension agents being withdrawn to the center and forestry extension workers managing it by the provinces together with the center. This has reduced the number of agricultural extension workers in East Lampung Regency, so that it is increasingly difficult to fulfill the target of implementing one village one extension agricultural extension worker. The next implication is that the range of extension services has expanded with a total of 264 villages and a total of 6,233 farmer groups served only by 112 agricultural extension workers. Another problem is the agricultural extension policy under the local government which results in the implementation and management of agricultural extension activities encountering many obstacles. This research was conducted in East Lampung Regency. Data collection was carried out in November-December 2022. Respondents were 88 agricultural extension workers on duty in East Lampung Regency. This study used a survey method with a quantitative descriptive approach. The results showed that the perceptions of agricultural extension workers regarding the implementation of Law Number 23 of 2014 in East Lampung Regency were not good.